Building a data sharing model for global genomic research. - Kosseim, P; Dove, E; Baggaley, C; Meslin, E; Cate, F; Kaye, J; Harris, JR; Knoppers, B (2014)
Data sharing models designed to facilitate global business provide insights for improving transborder genomic data sharing. We argue that a flexible, externally endorsed, multilateral arrangement, combined with an objective third-party assurance mechanism, can effectively balance privacy with the need to share genomic data globally.